1985
DOI: 10.1177/0148607185009005583
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Skeletal Muscle Intracellular Glutamine during Standard Surgical Trauma

Abstract: Skeletal muscle glutamine (GLN) concentration falls following injury and infection. In an attempt to prevent this decline and to characterize its influence on the efflux of amino acid (AA) from skeletal muscle, we administered varying quantities of AA (0,2, and 4 g/kg X day) as saline or AA solutions with or without GLN enrichment to 22 postoperative dogs. Plasma and muscle AA were determined before and 24 hr after standard laparotomy. Hindquarter AA efflux was measured at 6 and 24 hr. Skeletal muscle nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Similarly, the alanine and glutamine concentration in the artery (29.8 vs.28.8%) declined more than that in the vein (12.3 vs. 19.1%) and muscle compartments (4.1 vs. 4.7%). Human and animal studies have suggested that the muscle glutamine pool positively influences protein synthesis (24,27). Furthermore, it is claimed that this correlation is specific for glutamine and has not been observed with any other amino acid (32).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the alanine and glutamine concentration in the artery (29.8 vs.28.8%) declined more than that in the vein (12.3 vs. 19.1%) and muscle compartments (4.1 vs. 4.7%). Human and animal studies have suggested that the muscle glutamine pool positively influences protein synthesis (24,27). Furthermore, it is claimed that this correlation is specific for glutamine and has not been observed with any other amino acid (32).…”
Section: Discussionmentioning
confidence: 99%
“…There is a striking direct correlation between glutamine concentration and the rate of protein synthesis in rat skeletal muscle in vivo (Jepson et al 1988). Glutamine infusions can reduce the post-operative efflux of amino acids for dog hind limb (Kapadia et al 1985) and can directly stimulate protein synthesis (MacLennon ef al. 1987) and inhibit protein degradation (MacLennon et al 1988) in muscle.…”
Section: Glutaminementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Toxicity to the tumorbearing host is seen from the disease and from chemotherapy treatment-related injury. Dose intensification of chemotherapy is thought to increase survival.9"'0 However, the limitation of intensifying chemotherapeutic regimens has become the severity of toxicity to the normal host tissues.'…”
mentioning
confidence: 99%
“…'7 Glutathione is a potent ubiquitous antioxidant that also is an important factor in the metabolism of many drugs and endogenous substances. 8 '9 An important function of GSH is protection of critical cellular molecules. Toxicity of target tissue is a result of depletion oftissue GSH concentration and protein alkylation.…”
mentioning
confidence: 99%